A critical evaluation of measurement induced variability in infiltration characteristics for a river sub-catchment. (January 2019) - Ghosh, Biplab; Pekkat, Sreeja
Highlights: Comparative assessment of infiltrometers based on measured infiltration rate curves. Proposed non-linear asymptotic curve for normalized infiltration rate curve. The initial water content exhibits negative correlation with infiltration. Particle size fraction have insignificant correlation with infiltration. Infiltration determined by disc infiltrometer is 2/3rd of double ring infiltrometer. Abstract: Infiltration measurements are important for the hydrological modelling of catchment. Different methodologies adopted for measurements exhibit variability in infiltration characterization, which needs to be studied in detail. This study compared the infiltration characteristics measured using double ring infiltrometer (DRI), mini-disc Infiltrometer (MDI) and tension disc infiltrometer (TI) for identical field conditions and two seasons within a river sub-catchment in north-east India. It was noted that the initial infiltration rate (ii ) was highest and final infiltration rate (if ) was lowest for DRI while in most of the cases it was comparable for disc infiltrometers. The study proposed normalized infiltration rate curves for alleviating instrument related variabilities for comparing infiltration measurements performed using different infiltrometers. A non-linear asymptotic curve adequately represent the normalized infiltration rate curve as compared to the Horton form of infiltration equation. Statistical evaluation of the measured results indicates that initial water content exhibits a negative correlation and particle size fraction have statistically insignificant correlation with hydraulic conductivity (Kh0 ) determined from infiltrometers. Further, Kh0 exhibited a positive correlation with all the infiltration characteristics with higher correlation coefficient for ii, and (ii − if ). The Kh0 determined by disc infiltrometers (MDI and TI) are found to be approximately two-thirds of DRI values. The study clearly demonstrates the usefulness of disc infiltrometers vis-à-vis DRI for rigorous and repeatable measurements for establishing near saturated infiltration characteristics at catchment scale.